Application of Mind Map to Organize Ideas in Learning Insya Hurr at Miftahul Ulum Islamic Boarding School - Salsabilah, Salsabilah; Albantani, Azkia Muharom (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This research aims to investigates the effectiveness of using Mind Maps to organize ideas in learning insya hurr. A quasi-experimental design with a non-equivalent control group was employed. The participants were from 11th-grade students at Miftahul Ulum Islamic Boarding School, divided into an experimental group (15 students) and a control group (14 students). Data were collected through pre-tests, post-tests, and observations. The analysis was performed using the Shapiro-Wilk normality test, homogeneity test, Independent Sample t-test, and N-Gain test with SPSS 23. The results indicate that Mind Maps effectively enhanced independent writing skills. The experimental group achieved a higher average post-test score (83.13) compared to the control group (71.64). Hypothesis testing using the t-test yielded a value of 9.111, which exceeded the critical value of 2.052, leading to the rejection of H₀ and acceptance of Hₐ. This finding confirms that Mind Maps are an effective tool for organizing ideas and improving writing skills in teaching insya hurr at Miftahul Ulum Islamic Boarding School.